Sexual Dimorphic Distribution of Hypothalamic Tachykinin1 Cells and Their Innervations to GnRH Neurons in the Zebrafish - Ogawa, Satoshi; Ramadasan, Priveena Nair; Anthonysamy, Rachel; Parhar, Ishwar S. (Frontiers in Endocrinology, 2021)
Substance P (SP) and neurokinin A (NKA), encoded by TAC1/Tac1 gene are members of the tachykinin family, which exert their neuromodulatory roles in vertebrate reproduction. In mammals, SP and NKA have been shown to regulate gonadotropin-releasing hormone (GnRH) and luteinizing hormone (LH) secretion via kisspeptin neurons. On the other hand, the role of SP/NKA in the regulation of reproduction in non-mammalian vertebrates is not well known. In the present study, we first localized expression of tac1 mRNA in the brain of male and female zebrafish, Danio rerio. Next, using an antibody against zebrafish tachykinin1 (Tac1), we examined the neural association of SP/NKA neural processes with GnRH3 neurons, and with kisspeptin (kiss2) neurons, in the brains of male and female zebrafish. In situ hybridization showed an apparent male-dominant tac1 expression in the ventral telencephalic area, the anterior and posterior parts of the parvocellular preoptic nucleus, and the suprachiasmatic nucleus. On the other hand, there was female-dominant tac1 expression in the ventral periventricular hypothalamus. Confocal images of double-labelled zebrafish Tac1 and GnRH3 showed associations between Tac1-immunoreactive processes and GnRH3 neurons in the ventral telencephalic area. In contrast, there was no apparent proximity of Tac1 processes to kiss2 mRNA-expressing neurons in the hypothalamus. Lastly, to elucidate possible direct action of SP/NKA on GnRH3 or Kiss2 neurons, expression of SP/NKA receptor, tacr1a mRNA was examined in regions containing GnRH3 or Kiss2 neurons by in situ hybridization. Expression of tacr1a mRNA was seen in several brain regions including the olfactory bulb, preoptic area and hypothalamus, where GnRH3 and Kiss2 cells are present. These results suggest that unlike in mammals, Tac1 may be involved in male reproductive functions via direct action on GnRH3 neurons but independent of kisspeptin in the zebrafish.